Financial, Exchange Rate, and Wage Policies in Singapore, 1979-1886. (IMF Working Papers; Working Paper ;, 1988)
This paper discusses the unique aspects of Singapore's financial, exchange rate, and wage policies during the period 1979-86, and attempts to quantify the impact of alternative policies on major macroeconomic variables. For this purpose, a simple short-term model is formulated and estimated, and various policy simulations conducted. It is found that the wage policy pursued by the authorities in the early 1980s played a significant role in influencing output and prices and that an appropriate wage policy is complementary to exchange rate policy in maintaining external competitiveness in Singapore.